Kajian Yuridis Terhadap Cryptocurrency Ilegal Dalam Prespektif Tindak Pidana Pencucian Uang - Getri Kefi; Aksi Sinurat; Orpa G.Manuain (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to find out what are the forms of modes in the crime of Money Laundering Using Illegal Cryptocurrency Media as well as Criminal Law policies in an effort to overcome the occurrence of Money Laundering Crimes through illegal Cryptocurrency Media. To answer the above problems, this Research Method uses the Normative Law research method which focuses on research on written regulations or legislation or research based on rules or norms that apply in society. The results of the discussion in this study show that, (1) The mode of operation used by the perpetrators in the crime of money laundering through Cryptocurrency media is by trading and investment methods along with several other methods. The perpetrators take advantage of the transaction system on cryptocurrencies that are closed or anonymous so that the perpetrators get an opening to launch criminal acts. 2) Even with existing legal regulations, there are still criminal acts, especially TPPU which are carried out through illegal cryptocurrencies, so it is better for the government to make rules or make legal updates on how to process related to Money Laundering Crimes using cryptocurrencies which include crypto platforms, both legal and illegal.